Optimization of Sustainable Development Based on Triple Bottom Line Theory - Roki' Khairullah; Mohammad Sodik; Hartini Prasetyaning Pawestri (Journal of Management Research and Studies, 2024)
This research aims to analyze the implementation of Green Accounting based on Triple Bottom Line Theory in supporting Sustainable Development in the Bumdes "Sumber Sejahtera" Pujon Kidul Tourism Village. This research uses a qualitative descriptive approach with observation, interviews and documentation methods. Based on the results of interviews and data analysis, in implementing Green Accounting at BUMDes Sumber Sejahtera in its business there is bookkeeping related to social, environmental and economic activities. The efforts made by BUMDes Sumber Sejahtera do not yet reflect true green accounting. However, from the ecological, monetary and social aspects of the activities carried out by the organization, it can be said that they are in accordance with the Triple bottom line form and support Sustainability development.